PERBANDINGAN MORFOMETRIK KUDA DI KECAMATAN TOMPASO BARAT DAN DI NUSANTARA POLO CLUB BOGOR JAWA BARAT - Turangan, Grantino F.; Paputungan, Umar; Poli, Zulkifli; Lomboan, Agustinus (Universitas Sam Ratulangi, 2017)
This study was done to evaluate the phenotypic comparison of the body measurements for genetic improvement of running horses at West Tompaso district and those at Nusantara Polo Club Bogor West Java.. Total of forty four running horses consisted of twenty two horses from Nusantara Polo Club Bogor and twenty two horses from West Tompaso district were used in this study. Observation was conducted on November 2016 - January 2017 using purposive sampling method to measure body size of horses. The pregnant horses were excluded in this. The variables measured in this study were including chest girth, chest wide, chest depth, shoulder height, hip height, hip wide, body length, neck length, head wide, and head length. Results showed that body measurements of horses at West Tompaso district tended bigger in the sizes of hip wide, head wide and head length compared with those of horses at Nusantara Polo Club Bogor West Java. While, the body measurements of horses at Nusantara Polo Club Bogor West Java tended bigger in the sizes of chest girth, shoulder height, body length and neck length compared with those at West Tompaso district.Key words: Morfometrik, horse